PROMOTION DESIGN OF GRIYA BATIK BROTOSENO, SRAGEN DISTRICT - Sanjaya, Rangga Tri (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2019)
Griya Batik Brotoseno is the oldest batik central in Kliwonan village. It is established since 1974 by Mr. H. Suprajan with an address in Kuyang, Kliwonan village, Masaran sprouts, Sragen district, Central Java. The effective and efficient Batik Brotoseno for promoting and boosting sales so Batik Brotoseno can survive in stiff competition. Promotion media designing methods is conducted by analyzing, target audience, then find an idea and consult with the client, and then for the production process are preparing tools, sketching, promotion media designing, printing and prototyping the works, and determining the placement or media targets. Promotion media is designed by improving the exist media such as brochure, bill, stationery set, kemasan and adding merchandise. In promotion media is applied of visual elements of batik flora and fauna motives were lifted by Griya Batik Brotoseno.